Predictors of hospital-based multidisciplinary rehabilitation effects in persons with multiple sclerosis: a large-scale, single-centre study. Issue 2 (April 2019) - Groppo, Elisabetta; Signori, Alessio; Sormani, Maria Pia; Grosso, Cristina; Mantia, Loredana La; Cattaneo, Davide; Rovaris, Marco
Background: Persons with multiple sclerosis may benefit from hospital-based multidisciplinary rehabilitation. Objectives: To investigate the effects of hospital-based multidisciplinary rehabilitation and to identify their potential predictors in a large sample of persons with multiple sclerosis. Methods: From the charts of 655 persons with multiple sclerosis consecutively admitted to our unit, disease profiles, modified Barthel index, Expanded Disability Status Scale (EDSS), pain numerical rating score and type of interventions were retrospectively collected. We defined an improvement at discharge as follows: modified Barthel index increase of at least 5 points, EDSS decrease of 1.0 if baseline score was 5.5 or less and of 0.5 if baseline score was greater than 5.5; any numerical rating score decrease. Results: After a median admission period of 36 days, at discharge 65%, 22% and 89% of persons with multiple sclerosis improved for modified Barthel index, EDSS and numerical rating score, respectively. The modified Barthel index improvement was associated with shorter disease duration, lower EDSS at baseline and with access to psychological counselling. EDSS improvement was associated with shorter disease duration, relapsing–remitting course, female gender and longer duration of the admission period. Conclusions: Inpatient multidisciplinary rehabilitation was associated with improved autonomy in activities of daily living in a relevant proportion of persons with multiple sclerosis. The effect seems to be more evident in individuals with shorter multiple sclerosis duration and relapsing–remitting disease course.